Semen characteristics and cryopreservation in bornean sun bear (helarctos malayanus euryspilus) - Yeoh, Boon Nie (2023)
The Bornean sun bear (Helarctos malayanus euryspilus) is the subspecies of the Malayan sun bear that is endemic to Borneo island. The species is endangered not just because of anthropogenic threats, but also experiencing slow reproductive rates both in the wild and in captivity. When conservation breeding is considered, assisted reproductive technology (ART) could be a fundamental alternative tool to propagate the species population in captivity. This study is a pioneering work examining the semen characteristics of the Bornean sun bear and attempting its semen cryopreservation as a means of genome resource storage. Semen collection was achievable via electroejaculation in ten sun bears. An ejaculator probe (2.5 cm in diameter and 7.0 cm in length) was inserted rectally and positioned dorsal to the palpable prostate gland. The optimum voltage to obtain semen differed with each individual, but all manifested with bilateral hindlegs contractions and penile erection before ejaculation. The combined testicular volume in the Bornean sun bear was 23.37 ± 5.09 cm³. From the 30 good quality semen, the average semen traits were pH 7.79, volume of 617.3 μL with sperm concentration at 1034.40 x 10⁶ sperm/mL. Sperm viability was 80.19% with motility and progressive movement at 79.13% and 70.20% respectively. The high sperm abnormalities at 70.67% could be a normal feature in the Bornean sun bear. Sun bear’s spermatozoon was 61.28 ± 2.46 μm in length and consists of an oval head, midpiece, and tail. Collected semen was cryopreserved with Caniplus Freezing Medium semen extender with the slow freezing protocol. Post-thaw semen quality, however, was compromised with poor viability (27.57%), motility (8.30%), and progressive movement (1.32%). Other than conventional semen evaluation, Computer-Assisted Sperm Analysis and additional functional tests including the evaluation of acrosome (Rose Bengal Fast Green stain), plasma membrane (Hypoosmotic swelling test), and chromatin (Toluidine Blue stain) had proven valuable in assessing semen characteristics. From this study, good semen donors were identified from the captive Bornean sun bear population. This finding supports the conservation value of captive management that at least male reproductive functions are not compromised. The established baseline data of semen characteristics serves as the crucial reference for artificial insemination in the future. Further research to optimize and develop species-specific cryopreservation protocols are essential. Other ART practices such as in-vitro fertilization, and more importantly, intracytoplasmic sperm injection are suggested as the following efforts to make use of the valuable frozen-thawed semen.